2006
DOI: 10.3200/jmbr.38.6.431-137
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Movement Strategies Using a Computer-Pointing Task

Abstract: Females typically demonstrate a movement time advantage for tasks requiring high levels of manual dexterity, whereas males are notably better at targeting activities. According to D. Kimura (2000), the hunter-gatherer hypothesis primarily accounts for those performance advantages; that dichotomy fails, however, when one makes movement outcome predictions for tasks that are not clearly fine-motor or interceptive in nature. Investigators have recently proposed that time constraints (M. Peters, 2005) and gender-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 29 publications
2
34
3
Order By: Relevance
“…What is more, for the right placed panels men outperformed women in both bottom and top panel locations, so the interaction did not exist. Taking into consideration only the right locations, the present research outcomes to some extent support the assumption that men do better where the task accomplishment time is evaluated (Ives et al, 1993;Peters & Campagnaro, 1996;Warshawsky-Livne & Shinar, 2002;Barral & Debû 2004;Rohr, 2006aRohr, , 2006b. But the differences are not statistically significant (df = 1, W = 1.34, p = 0.247).…”
Section: Gender Differencessupporting
confidence: 59%
See 1 more Smart Citation
“…What is more, for the right placed panels men outperformed women in both bottom and top panel locations, so the interaction did not exist. Taking into consideration only the right locations, the present research outcomes to some extent support the assumption that men do better where the task accomplishment time is evaluated (Ives et al, 1993;Peters & Campagnaro, 1996;Warshawsky-Livne & Shinar, 2002;Barral & Debû 2004;Rohr, 2006aRohr, , 2006b. But the differences are not statistically significant (df = 1, W = 1.34, p = 0.247).…”
Section: Gender Differencessupporting
confidence: 59%
“…When the discrepancies in accomplishing simple pointing activities are concerned, it is assumed that they are a result of different strategies used by both sexes. According to this approach, women perform better when the accuracy is analysed, while men are superior in tasks, where completion time is of a great concern (Ives et al, 1993;Peters & Campagnaro, 1996;Warshawsky-Livne & Shinar, 2002;Barral & Debû 2004;Rohr, 2006aRohr, , 2006b. As it was outlined above, there has been a significant amount of research regarding gender differences in performing cognitive and motor tasks separately, however the studies treating these two conditions simultaneously are hardly to find.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there was no gender difference. Although men perform better to the tasks, where completion time is mainly concerned [17], our result does not support this claim. By measuring least square means about the accuracy (Figure 4(a)) and the time spent (Figure 4(a)), participants spent more time when solving more difficult task questions (difficulty of each task: task 1 < task 2 < task 3).…”
Section: A Quantitative Analysiscontrasting
confidence: 92%
“…About 69.4% of male participants correctly solved the given tasks; whereas only about 50.4% of female participants provided correct answers. Rohr [17] conducted a study to see the gender difference when performing a computer-pointing task. From the study, she found that women perform better when accuracy is analyzed.…”
Section: A Quantitative Analysismentioning
confidence: 99%
“…However, when Rohr 8 applied a discrete aiming task with a fixed demand of speed, no interaction between task difficulty and sex was found for MT. Similarly, Rohr 18 and Teeken et al, 6 found no difference in MT between sexes in a reciprocal aiming task, but found a difference in a discrete aiming task. However, similar to our study Teeken et al, 6 instructed the participants to move as quickly and accurately as possible.…”
Section: Discussionmentioning
confidence: 87%